Cytochrome c1 in ductal carcinoma in situ of breast associated with proliferation and comedo necrosis. Issue 7 (19th May 2017) - Chishiki, Mayuko; Takagi, Kiyoshi; Sato, Ai; Miki, Yasuhiro; Yamamoto, Yuta; Ebata, Akiko; Shibahara, Yukiko; Watanabe, Mika; Ishida, Takanori; Sasano, Hironobu; Suzuki, Takashi
Abstract : This is the first report that examined CYC1 in ductal carcinoma in situ (DCIS) of the human breast. CYC1 immunoreactivity was associated with comedo necrosis and Ki‐67 in DCIS tissues, and CYC1 was significantly associated with mitochondrial membrane potential, proliferation activity and pro‐apoptotic caspase 3 activity under hypoxia in DCIS cells. Our present results suggest that CYC1 is associated with aggressive phenotype of DCIS through promoting mitochondrial oxidative phosporylation activity and it could become an important therapeutic target of breast cancer patients. Abstract : It is well known that comedo necrosis is closely associated with an aggressive phenotype of ductal carcinoma in situ (DCIS) of human breast, but its molecular mechanisms remain largely unclear. Therefore, in this study, we first examined the gene expression profile of comedo DCIS based on microarray data and identified CYC1 as a gene associated with comedo necrosis. Cytochrome c1 (CYC1) is a subunit of complex III in the mitochondrial oxidative phosphorylation that is involved in energy production. However, the significance of CYC1 has not yet been examined in DCIS. We therefore immunolocalized CYC1 in 47 DCIS cases. CYC1 immunoreactivity was detected in 40% of DCIS cases, and the immunohistochemical CYC1 status was significantly associated with tumor size, nuclear grade, comedo necrosis, van Nuys classification, and Ki‐67 labeling index. Subsequent in vitro studies indicated that CYC1 was significantly associated with mitochondrial membrane potential in MCF10DCIS.com DCIS cells. Moreover, CYC1 significantly promoted proliferation activity of MCF10DCIS.com cells and the cells transfected with CYC1 siRNA decreased pro‐apoptotic caspase 3 activity under hypoxic or anoxic conditions. Considering that the center of DCIS is poorly oxygenated, these results indicate that CYC1 plays important roles in cell proliferation and comedo necrosis through the elevated oxidative phosphorylation activity in human DCIS.